Aluminum-silicon co-permeation coating based on Hf modification and preparation method of aluminum-silicon co-permeation coating

By mixing the solid osmosis and liquid phase component in aluminum silicon coating, the HF modified aluminum silicon co -coating is formed, which solves the unevenness of the component distribution and the poor antioxidant performance. The problem realizes efficient and controllable coating preparation and excellent antioxidant performance.

CN119372587AActive Publication Date: 2025-01-28XIAN THERMAL POWER RES INST CO LTD +1

Patent Information

Application Number
CN202411286451.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-28
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

In aluminum-silicon co-permeable coating, the doping of Hf may lead to uneven distribution of components, affecting the antioxidant performance of the coating. In the existing processes, there are difficulties in controlling the rate of oxide generation, problems with the binding force of the coating and the substrate, and coating Defects such as surface quality problems and production process complexity and cost.

Method used

Through the ball grinding, the solid seepage is obtained. After the mixed liquid phase components, stir up and grind again to form the coating, spray it on the surface of the preheated workpiece, natural air dry and low temperature solidification, and finally heat treatment in an inert atmosphere. Form -based aluminum silicon co -exudation based on HF modification.

Benefits of technology

Effectively avoid the phenomenon of oxidation, hydrogen brief, improve the infiltration and coating antioxidant capacity, enhance the intensity of the binding of the slurry layer and the surface of the workpiece, and improve the control of the preparation efficiency and process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372587A_ABST
    Figure CN119372587A_ABST
Patent Text Reader

Abstract

According to the aluminum-silicon co-permeation coating based on Hf modification and the preparation method of the aluminum-silicon co-permeation coating, the coating is prepared through heat treatment under the inert atmosphere, the phenomena of oxidation, hydrogen embrittlement and the like possibly occurring in austenitic steel are effectively avoided, the permeation speed is increased while a workpiece base body is protected, and the service life of the coating is prolonged. By means of the segmented slurry curing process combining natural air drying and medium-low temperature curing, the problems of micro cracks and tiny holes generated by a slurry layer due to thermal stress during direct drying are effectively solved, the bonding strength of the slurry layer and the surface of a workpiece is enhanced, and rapid evaporation of slurry components at the high temperature is prevented; the workpiece is subjected to heat treatment through rapid heating and short-time heat preservation, the overall preparation production efficiency is high, the thickness is controllable, the method is suitable for metal workpieces of various complex shapes, the technology repeatability is high, and extremely high practicability and universality are achieved; therefore, the thermal corrosion resistance of the coating is improved, and the anti-stripping performance of the oxide film is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface alloying and coating, and specifically relates to an aluminum-silicon co-penetration coating based on Hf modification and a preparation method thereof. Background Art

[0002] Al film is formed on the alloy surface by Al infiltration. The compactness of aluminum oxide prevents water vapor from corroding the substrate. Si infiltration improves the corrosion resistance of the substrate. The combination of the two improves the overall corrosion resistance. Due to the influence of high-temperature working environment, the generation rate of oxide on the coating surface is relatively fast. A large amount of Al reacts with air, which affects the strength of the coating surface. When the thickness of the oxide layer on the coating surface reaches a certain range, the high-temperature anti-corrosion effect of the coating decreases. If the oxide falls off during use, thermal power pipelines will be blocked and pipes will explode.

[0003] As an active element, Hf has special advantages in high-temperature anti-oxidation work. During the doping process, Hf reacts with oxygen in the air to generate oxides, which are unevenly distributed inside the coating, playing a role in pinning and hindering component segregation. Since Hf can hinder the diffusion of Al, the generation rate of Al2O3 is greatly slowed down, which greatly increases the service life of the oxide layer.

[0004] However, during the Al-Si co-penetration process, Hf doping may lead to uneven distribution of components within the coating. The high activity of the Hf element may cause its distribution in the coating to be locally enriched, which will lead to differences in the coating's oxidation resistance, that is, some areas have strong oxidation resistance, while other areas are relatively weak. In other words, although the Hf-doped Al-Si co-penetration coating has the potential to improve the high-temperature corrosion and oxidation resistance of the alloy in theory, it still has defects such as uneven composition, difficulty in controlling the oxide generation rate, problems with the bonding strength of the coating and the substrate, problems with the surface quality of the coating, and complexity and cost of the preparation process in the actual preparation process. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an aluminum-silicon co-diffusion coating based on Hf modification.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0009] The solid phase component is ball-milled to obtain a solid phase penetrant, and the solid phase penetrant is mixed with the liquid phase component, stirred sufficiently, and then ball-milled to obtain a coating slurry;

[0010] The coating slurry is sprayed onto the preheated surface of the workpiece to be treated, and then naturally dried and cured to obtain a coated workpiece;

[0011] The coated workpiece is subjected to heat treatment and post-treatment in sequence, and is naturally air-dried to form an aluminum-silicon co-diffusion coating based on Hf modification on the surface of the workpiece;

[0012] Wherein, the solid phase components include, by mass percentage, 40-70% Al, 15-30% Si, 10-20% Al2O3, 2-5% NH4Cl, and 3-7% Hf;

[0013] The liquid phase components include, by mass percentage, an Al(H2PO4)3 solution with a mass concentration of 70 to 90% and a CrO3 solution with a mass concentration of 10 to 30%, wherein the mass ratio of the Al(H2PO4)3 solution to the CrO3 solution is 1:0.8 to 1.2.

[0014] As a preferred solution of the method for preparing the Hf-modified aluminum-silicon co-penetration coating according to the present invention, the ball milling speed of the solid phase component is 350-400 rpm, and the ball milling time is 8-12 h.

[0015] As a preferred scheme for the preparation method of the Hf-modified aluminum-silicon co-penetration coating described in the present invention, the sufficient stirring time after the solid-phase penetrant and the liquid-phase component are mixed is 2 to 4 hours, wherein the solid-liquid ratio of the solid-phase penetrant to the liquid-phase component is 10g:4 to 6ml.

[0016] As a preferred solution of the method for preparing the Hf-modified aluminum-silicon co-penetration coating according to the present invention, the ball milling speed after the solid phase penetrant and the liquid phase component are mixed is 350-400 rpm, and the ball milling time is 8-12 hours.

[0017] As a preferred solution of the preparation method of the Hf-modified aluminum-silicon co-diffusion coating according to the present invention, the preheating condition of the workpiece to be processed is medium frequency preheating at 200-250°C for 30-60 minutes.

[0018] As a preferred solution of the preparation method of the Hf-modified aluminum-silicon co-diffusion coating described in the present invention, the spraying pressure of the coating slurry is 0.5-2MPa, the thickness of the coating layer after spraying is 0.1-5mm, and the coating layer coverage of the workpiece is >98%.

[0019] As a preferred solution of the preparation method of the Hf-modified aluminum-silicon co-diffusion coating according to the present invention, the curing temperature is 300 to 450° C. and the curing time is 24 to 48 hours.

[0020] As a preferred scheme of the preparation method of the Hf-modified aluminum-silicon co-diffusion coating described in the present invention, the heat treatment is carried out under inert gas conditions, the heat treatment temperature is 980-1150°C, the heat treatment time is 8-15 minutes, and the inert gas includes Ar or N2.

[0021] Another object of the present invention is to provide an aluminum-silicon co-diffusion coating based on Hf modification.

[0022] As a preferred solution of the Hf-modified aluminum-silicon co-penetration coating of the present invention, the thickness of the aluminum-silicon co-penetration coating is 25-48 μm, and the Al atomic content is 25%-40%.

[0023] As a preferred solution of the Hf-modified aluminum-silicon co-diffusion coating described in the present invention, the aluminum-silicon co-diffusion coating has an antioxidant capacity that is 19 to 65 times higher than that of the base material in a 600°C pure water vapor environment; and an antioxidant capacity that is 20 to 78 times higher than that of the base material in a 650°C pure water vapor environment.

[0024] Beneficial effects of the present invention:

[0025] The preparation method of the Hf-modified aluminum-silicon co-diffusion coating provided by the present invention effectively avoids the oxidation, hydrogen embrittlement and other phenomena that may occur in austenitic steel by heat treatment under an inert atmosphere, protects the workpiece matrix while improving the infiltration rate, and effectively avoids the microcracks and tiny holes in the slurry layer caused by thermal stress during direct drying through a segmented slurry curing process combining natural air drying with medium and low temperature curing, and enhances the bonding strength between the slurry layer and the workpiece surface. In order to prevent the rapid evaporation of the slurry components at high temperature, the workpiece is heat treated by rapid heating and short-time heat preservation. The overall preparation production efficiency is high and the thickness is controllable. It is suitable for metal workpieces of various complex shapes, the process has high repeatability, and has extremely strong practicality and universality.

[0026] In addition, by adding halide NH4Cl to the slurry component, it has the effect of catalyzing and activating the infiltration, thereby improving the infiltration rate and coating quality; by adding Hf to the infiltrant, HfO2 can be formed during oxidation, which can pin the oxide film to prevent it from falling off, thereby improving the bonding strength between the oxide film and the substrate, and by introducing the Si element to modify the alumina anti-oxidation coating, the coating's resistance to thermal corrosion is improved. Furthermore, by introducing the Hf element for modification, it can aggregate at the oxide grain boundaries and hinder further oxidation of the parent material. Its oxidation product HfO2 can pin the oxide film and enhance the oxide film's anti-flaking performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0028] Figure 1 This is a cross-sectional morphology diagram of the Hf-modified aluminum-silicon co-diffusion coating formed on the surface of the workpiece according to Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The raw materials used in the present invention are all commercially available in the art unless otherwise specified, wherein the Al, Si, and Hf powders of the solid phase components are all sieved through a 1000-mesh sieve.

[0033] The base workpiece used in the present invention is TP347H.

[0034] Example 1

[0035] This embodiment provides a method for preparing an aluminum-silicon co-penetration coating based on Hf modification, specifically:

[0036] 1) Prepare coating slurry:

[0037] Weigh the solid phase components according to the following ratio:

[0038] 40% Al, 30% Si, 20% Al2O3, 5% NH4Cl, 5% Hf;

[0039] The weighed solid phase components were placed in a planetary ball mill at 400 rpm for 12 h to obtain a solid phase penetration agent;

[0040] Prepare Al(H2PO4)3 solution with a mass concentration of 85% and CrO3 solution with a mass concentration of 15%, mix them in a mass ratio of 1:1, and obtain a liquid phase component after sufficient mixing, stirring, reaction and filtering for 8 hours;

[0041] The solid and liquid components were mixed at a solid-liquid ratio of 10 g:5 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 12 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0042] 2) Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone;

[0043] The workpiece was preheated at 250°C for 45 minutes by medium frequency, and the slurry was coated at a spraying pressure of 1 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%, followed by natural air drying for 48 hours and curing at 450°C for 48 hours to obtain a coated workpiece.

[0044] 3) The coated workpiece is placed under Ar for heat treatment at a temperature of 1000°C and a holding time of 15 min. After treatment, the residue on the surface of the workpiece is washed with a high-pressure water gun and naturally air-dried to form an aluminum-silicon co-diffusion coating based on Hf modification on the surface of the workpiece. The cross-sectional morphology of the diffusion layer is as follows: Figure 1 shown.

[0045] The mass change data of the coating prepared in Test Example 1 in a steam oxidation test in water vapor at 600°C and 650°C for 1000h were compared with the workpiece substrate. The results are shown in Tables 1 and 2.

[0046] Table 1 Mass change data of TP347H and TP347H coating in 600℃ water vapor

[0047]

[0048] Table 2 Mass change data of TP347H and TP347H coating in 650℃ water vapor

[0049]

[0050] It can be seen from the data in Tables 1 and 2 that the aluminum-silicon coating obtained in the embodiment of the present invention has an antioxidant capacity that is 19 to 65 times higher than that of the base material in a 600°C pure water vapor environment, and an antioxidant capacity that is 20 to 78 times higher than that of the base material in a 650°C pure water vapor environment. This indicates that the aluminum-silicon antioxidant coating prepared by the method of the present invention effectively improves the antioxidant capacity of the alloy base material in a water vapor environment.

[0051] Comparative Example 1

[0052] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0053] 40% Al, 30% Si, 25% Al2O3, 5% NH4Cl;

[0054] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0055] The mass change data of the coating prepared in this comparative example was tested in a steam oxidation test in 600°C water vapor for 1000 hours and compared with the workpiece substrate. The results are shown in Table 3.

[0056] Table 3 Mass change data of TP347H and TP347H coating in 600℃ water vapor

[0057]

[0058] It can be seen that the coating prepared without adding Hf has a certain improvement in oxidation resistance compared with the base material in a 600°C pure water vapor environment, but the improvement effect is greatly reduced compared with the embodiment. This is because the present invention introduces Hf element modification, which can aggregate at the oxide grain boundary and hinder further oxidation of the base material. Its oxidation product HfO2 can pin the oxide film and enhance the anti-stripping performance of the oxide film.

[0059] Example 2

[0060] The difference between this embodiment and embodiment 1 is that the solid-liquid ratio in step 1) is adjusted, and the processes of the remaining steps are all referred to embodiment 1, so that aluminum-silicon co-diffusion coatings with different solid-liquid ratios in this embodiment are obtained, and relevant diffusion layer parameters are measured. The results are shown in Table 4.

[0061] Table 4

[0062]

[0063] Example 3

[0064] The difference between this embodiment and embodiment 1 is that the spraying pressure in step 2) is adjusted, and the processes of the remaining steps are all referred to embodiment 1, so that the aluminum-silicon co-diffusion coatings with different spraying pressures in this embodiment are obtained, and the relevant diffusion layer parameters are measured. The results are shown in Table 5.

[0065] Table 5

[0066]

[0067] Example 4

[0068] The difference between this embodiment and embodiment 1 is that the curing conditions in step 2) are adjusted, and the processes of the remaining steps are all referred to embodiment 1, so that the aluminum-silicon co-diffusion coatings with different curing conditions of this embodiment are obtained, and the relevant diffusion layer parameters are measured. The results are shown in Table 6.

[0069] Table 6

[0070]

[0071] Example 5

[0072] The difference between this embodiment and embodiment 1 is that the heat treatment parameters in step 3) are adjusted, and the processes of the remaining steps are all referred to embodiment 1, so as to obtain the aluminum-silicon co-diffusion coating under different heat treatment parameters of this embodiment, and measure the relevant diffusion layer parameters, and the results are shown in Table 7.

[0073] Table 7

[0074]

[0075]

[0076] By analyzing and studying the above examples, it is measured that the thickness of the diffusion layer is about 25-48 μm, the Al atomic content is 25%-40%, and the cross-sectional morphology of the diffusion layer of Example 1 is as follows: Figure 1 As shown in Tables 1 to 4 and the cross-sectional morphology, it is found that the infiltration layer prepared by the method of the present invention has a uniform structure, a moderate thickness, sufficient diffusion of Al atoms, a good metallurgical bond between the infiltration layer and the substrate, and is not easy to fall off.

[0077] Example 6

[0078] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0079] 50% Al, 30% Si, 14% Al2O3, 2% NH4Cl, 4% Hf;

[0080] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0081] Example 7

[0082] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0083] 50% Al, 30% Si, 13% Al2O3, 2% NH4Cl, 5% Hf;

[0084] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0085] Example 8

[0086] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0087] 60% Al, 20% Si, 13% Al2O3, 2% NH4Cl, 5% Hf;

[0088] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0089] Example 9

[0090] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0091] 70% Al, 10% Si, 15% Al2O3, 2% NH4Cl, 3% Hf;

[0092] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0093] Example 10

[0094] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0095] 50% Al, 30% Si, 15% Al2O3, 2% NH4Cl, 3% Hf;

[0096] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0097] Comparative Example 2

[0098] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0099] 40% Al, 30% Si, 25% Al2O3, 5% Hf;

[0100] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0101] Comparative Example 3

[0102] The difference from Example 1 is that the solid phase component formula of step 1) is adjusted to:

[0103] 70% Al, 20% Al2O3, 5% NH4Cl, 5% Hf;

[0104] The remaining steps and processes are all referred to Example 1 to obtain the aluminum-silicon co-diffusion coating of this example.

[0105] The mass change data of the aluminum-silicon co-diffusion coatings of Examples 6 to 10 and Comparative Examples 2 and 3 after being exposed to 650°C water vapor for 1000 hours were measured, and the results are shown in Table 8.

[0106] Table 8 Mass change data after 1000h in 650℃ water vapor

[0107]

[0108] It can be seen from Table 8 that by adjusting the solid phase composition formula within a certain range, the obtained Al-Si co-diffusion coating can still have good antioxidant properties, but the coating performance is significantly reduced after omitting NH4Cl and Si.

[0109] In summary, the present invention adds halide NH4Cl to the slurry component to promote penetration and activation, thereby improving the penetration rate and coating quality; Hf is added to the penetrant to form HfO2 during oxidation, which can pin the oxide film to prevent it from falling off, thereby improving the bonding strength between the oxide film and the substrate. The present invention introduces Si element to modify the aluminide anti-oxidation coating, thereby improving the coating's resistance to thermal corrosion and having excellent economic benefits.

[0110] The present invention effectively avoids oxidation, hydrogen embrittlement and other phenomena that may occur in austenitic steel by heat treatment under an inert atmosphere, thereby protecting the workpiece substrate and improving the penetration rate; the present invention prepares the coating through an integrated slurry coating process production line, and the coating has high production efficiency and controllable thickness, is suitable for metal workpieces of various complex shapes, has high process repeatability, and has extremely strong practicality and universality.

[0111] Furthermore, the segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problems of microcracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface. In order to prevent the rapid evaporation of slurry components at high temperatures, the workpiece is heat treated by rapid heating and short-term insulation.

[0112] The Hf-modified aluminum-silicon anti-oxidation coating and the preparation method thereof in the present invention are suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes. They have strong practicality, high permeation rate, excellent membrane-base bonding, and excellent industrial mass production benefits.

[0113] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an aluminum-silicon co-penetration coating based on Hf modification, characterized in that: include, The solid phase component is ball-milled to obtain a solid phase penetrant, and the solid phase penetrant is mixed with the liquid phase component, stirred sufficiently, and then ball-milled to obtain a coating slurry; The coating slurry is sprayed onto the preheated surface of the workpiece to be treated, and then naturally dried and cured to obtain a coated workpiece; The coated workpiece is subjected to heat treatment and post-treatment in sequence, and is naturally air-dried to form an aluminum-silicon co-diffusion coating based on Hf modification on the surface of the workpiece; Wherein, the solid phase components include, by mass percentage, 40-70% Al, 15-30% Si, 10-20% Al2O3, 2-5% NH4Cl, and 3-7% Hf; The liquid phase components include, by mass percentage, an Al(H2PO4)3 solution with a mass concentration of 70 to 90% and a CrO3 solution with a mass concentration of 10 to 30%, wherein the mass ratio of the Al(H2PO4)3 solution to the CrO3 solution is 1:0.8 to 1.

2.

2. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 1, characterized in that: The ball milling speed of the solid phase component is 350-400 rpm, and the ball milling time is 8-12 hours.

3. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 1, characterized in that: The solid phase permeation agent and the liquid phase component are fully stirred for 2 to 4 hours after being mixed, wherein the solid-liquid ratio of the solid phase permeation agent to the liquid phase component is 10g:4 to 6ml.

4. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 3, characterized in that: The ball milling speed after the solid phase infiltration agent and the liquid phase component are mixed is 350-400 rpm, and the ball milling time is 8-12 hours.

5. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 1, characterized in that: The preheating condition of the workpiece to be processed is medium frequency preheating at 200-250° C. for 30-60 minutes.

6. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 1, characterized in that: The spraying pressure of the coating slurry is 0.5-2MPa, the thickness of the coating layer after spraying is 0.1-5mm, and the coating layer coverage of the workpiece is >98%.

7. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 1, characterized in that: The curing temperature is 300-450° C., and the curing time is 24-48 hours.

8. The method for preparing the Hf-modified aluminum-silicon co-penetration coating according to claim 1, characterized in that: The heat treatment is carried out under inert gas conditions, the heat treatment temperature is 980-1150° C., the heat treatment time is 8-15 minutes, and the inert gas includes Ar or N 2 .

9. The aluminum-silicon co-penetration coating prepared by the method for preparing an aluminum-silicon co-penetration coating based on Hf modification according to any one of claims 1 to 8, characterized in that: The thickness of the aluminum-silicon co-penetration coating is 25-48 μm, and the Al atomic content is 25%-40%.

10. The aluminum-silicon co-penetration coating according to claim 9, characterized in that: The aluminum-silicon co-diffusion coating has an oxidation resistance 19 to 65 times higher than that of the parent material in a 600°C pure water vapor environment; In a 650℃ pure water vapor environment, the antioxidant capacity is 20 to 78 times higher than that of the parent material.

Citation Information

Patent Citations

  • Penetrated layer thickness control method of aluminum-silicon co-penetration coating layer prepared by pulp method

    CN106119771A

  • Method for introducing rare metal Hf element into coating

    CN106283135A

  • Superalloy component and slurry composition

    CN107254659A

Cited By

  • Modification method for improving corrosion resistance of aluminide anti-oxidation coating

    CN120006279A